Sexagem de espermatozóides caninos em gradiente descontínuo de densidade: avaliação in vitro - Mothé, Gabriele Barros [UNESP] (2015)
Despite cytometry to be an effective method for sperm sexing, in dogs can be considered of difficult application, given the high cost of the technical implementation and low sperm recovery after separation. Therefore, this study aimed to evaluate the sperm viability, recovery rate and the percentage of sperm dogs containing the X or Y after centrifugation three discontinuous density gradients. Furthermore, aimed to study three DNA extraction techniques for sperm cells to determine the percentage of bearing cells of the X or Y chromosome for quantitative real-time PCR (qPCR). Thirty samples (10 dogs) of canine semen were evaluated using centrifugation discontinuous density gradient protocols (Percoll® - 30 to 90% associated to Nycodenz® and Ficoll). The sperm were evaluated before and after centrifugation for motility (CASA - Computer Aided Semen Analyzer), initial concentration and recovered concentration, sperm morphology, integrity of plasma and acrosomal membranes, and mitochondrial function. After separation, the cells were subjected to three DNA extraction protocols, a non-commercial using phenol:chloroform (M1) alone or combined with a preparatory kit (M2) and two commercial with extraction mini-columns (M3 and M4). Next, the DNA samples were subjected to qPCR using two primers (SRY - AF_107021.1 and Factor IX - NM_001003323.2). M1 protocol recovered greater concentration of DNA with higher quality and allowing the execution of qPCR. Among the density gradients, Ficoll maintained higher sperm quality after centrifugation, although the X or Y enrichment was not observed in any of the studied methods